Knowledge Enhancement on Lung Cancer and the Disease Prevention for People of Selokaton, Gondangrejo, Karanganyar - Mirah Rejeki; Umi Kartikawati (WARTA LPM, 2021)
Degenerative Disease contributes 63% of dead worldwide. It counts for 36 million people’s death every year. The prevalence number of the disease in Indonesia increases constantly. Lifestyle and food consumption habit are identified as two reasons why the disease takes place. One type of the diseases is cancer, where according to the data of World Health Organization, this is the second highest reason of death after cardiovascular disease. Type of cancer with the highest incidence and the top reason of death is lung cancer. In Karanganyar, according to the Health Department data, the occurrence of lung cancer increased from 1 case in 2016 to 5 cases in 2017. This increment alerts the urgent need for prevention and treatment of the disease. The lack of knowledge about lung cancer is the main reason leading to a possible high prevalence number. Based on the situation, the people knowledge about the lung cancer needs to be enhanced. This community development program was set up to achieve that objective through activity of presentation, discussion, and consultation. It involved 36 people in the age of 30-65 year old selected by the local government of Selokaton. The knowledge improvement of the attendees was assessed using pre-test and post-test. It was measured that the knowledge of participants increases from 4.58 at pre-test to 8.53 at post-test. This may indicate their interest on the program. It is expected that their knowledge will motivate then changing lifestyle in order to prevent the disease.